2010
DOI: 10.1007/s00216-010-3866-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the conditions for stripping voltammetric analysis at liquid–liquid interfaces supported at micropore arrays: a computational simulation

Abstract: Micropore membranes have been used to form arrays of microinterfaces between immiscible electrolyte solutions (µITIES) as a basis for the sensing of non-redox-active ions. Implementation of stripping voltammetry as a sensing method at these arrays of µITIES was applied recently to detect drugs and biomolecules at low concentrations. The present study uses computational simulation to investigate the optimum conditions for stripping voltammetric sensing at the µITIES array. In this scenario, the diffusion of ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…The steady-state behavior is also shown in the background-subtracted CV (Figure 1 B, inset). A similar phenomenon has been observed in the case of simple ion transfer at the mITIES, [19] for which, owing to the low diffusion coefficient in the viscous organic phase and the confined geometry defined by the micropore walls, the analyte accumulated in the organic phase close to the interface. The lack of a "diffusional tail" on this reverse peak suggests that diffusion of rA in the organogel phase is not the controlling step.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The steady-state behavior is also shown in the background-subtracted CV (Figure 1 B, inset). A similar phenomenon has been observed in the case of simple ion transfer at the mITIES, [19] for which, owing to the low diffusion coefficient in the viscous organic phase and the confined geometry defined by the micropore walls, the analyte accumulated in the organic phase close to the interface. The lack of a "diffusional tail" on this reverse peak suggests that diffusion of rA in the organogel phase is not the controlling step.…”
Section: Resultssupporting
confidence: 71%
“…As a result, it is hypothesized that rA transfers to the organic phase, where it accumulates, owing to its relatively large size (molecular mass 3.9 kDa) and low diffusion coefficient in the gelled organic phase, rather than diffusing away from the interface. A similar phenomenon has been observed in the case of simple ion transfer at the mITIES, [19] for which, owing to the low diffusion coefficient in the viscous organic phase and the confined geometry defined by the micropore walls, the analyte accumulated in the organic phase close to the interface. This accumulation effect may result in a thin layer of polypeptide in the organic gel, which is subsequently stripped back on the reverse sweep; however, the presence of an adsorbed layer cannot be fully excluded at present.…”
Section: Resultssupporting
confidence: 71%
“…The gel phase forms a recessed interface at the aqueous side of the ITIES (as it can be seen in figure1B). Computational simulations have shown that this configuration is optimal for stripping voltammetry, as transport of analyte species to the gel microinterface improves with a hemispherical diffusion regime during the preconcentration step [38] . Once they are transferred to the organic phase, they remain in the vicinity of the interface because of the reduced mass transport caused by both the linear diffusion and the lower diffusion coefficient in the PVC gel.…”
Section: System Characterization By Cyclic Voltammetry Analysismentioning
confidence: 99%
“…10,[15][16][17][18][19][20][21][22] Both ohmic drop and capacitive currents are dramatically diminished utilizing these ultra-small liquidliquid interfaces. For instance, nanopipets, micro and nanofabrication are used to develop massive sensor arrays.…”
Section: -14mentioning
confidence: 99%